2016
DOI: 10.1093/europace/euw215
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias in patients with Danon disease

Abstract: The present study indicates that the distinct surface ECG pattern in Danon disease is not associated with ventricular pre-excitation. Atrial fibrillation is frequently observed in these patients and may be associated with thromboembolic events in the young, while sustained ventricular arrhythmias occur less frequently than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…They concluded that one etiology for preexcitation pattern in these patients could have been FVP, although this was not confirmed. Interestingly, none of the female patients in their study had a WPW pattern although three out of four patients with preexcitation in our study were female …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…They concluded that one etiology for preexcitation pattern in these patients could have been FVP, although this was not confirmed. Interestingly, none of the female patients in their study had a WPW pattern although three out of four patients with preexcitation in our study were female …”
Section: Discussionmentioning
confidence: 93%
“…Conversely, in another series by Konrad et al, nearly all patients ( n = 7) with Danon disease had ventricular tachyarrhythmias leading to ICD placement ( n = 4). Nevertheless, none of these patients received an ICD therapy during a follow‐up period of nearly 4 years . These findings are similar to our study where placement of an ICD was performed for primary prevention based on nonsustained ventricular tachycardia, progressive septal hypertrophy and degree of fibrosis on cardiac MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms are not prominent and are frequently overlooked or misdiagnosed as simple hypertrophic cardiomyopathy. Heart failure is an important factor affecting the prognosis of patients with Danon disease (Konrad et al, 2017). Pathological changes in the muscles of patients with Danon disease include the presence of multiple membranous autophagy vacuoles (Stokes, Taylor, McLean, D'Arcy, & Mariani, 2016).…”
mentioning
confidence: 99%